The Age-Related Eye Disease 2 Study: Micronutrients in the Treatment of Macular Degeneration(1)(2)(3) - Gorusupudi, Aruna (Adv Nutr, 2017)
Age-related macular degeneration (AMD) is one of the leading causes of vision loss in the elderly. With an increasingly aged population worldwide, the need for the prevention of AMD is rising. Multiple studies investigating AMD with the use of animal models and cell culture have identified oxidative stress–related retinal damage as an important contributing factor. In general, diet is an excellent source of the antioxidants, vitamins, and minerals necessary for healthy living; moreover, the general public is often receptive to recommendations made by physicians and health care workers regarding diet and supplements as a means of empowering themselves to avoid common and worrisome ailments such as AMD, which has made epidemiologists and clinicians enthusiastic about dietary intervention studies. A wide variety of nutrients, such as minerals, vitamins, ω-3 (n–3) fatty acids, and various carotenoids, have been associated with reducing the risk of AMD. Initial results from the Age-Related Eye Disease Study (AREDS) indicated that supplementation with antioxidants (β-carotene and vitamins C and E) and zinc was associated with a reduced risk of AMD progression. The AREDS2 follow-up study, designed to improve upon the earlier formulation, tested the addition of lutein, zeaxanthin, and ω-3 fatty acids. In this review, we examine the science behind the nutritional factors included in these interventional studies and the reasons for considering their inclusion to lower the rate of AMD progression.